Prevalence and mechanisms of antimicrobial resistance in respiratory bacterial pathogens of ruminants: a systematic review - Peter, Sophia; Zulkiffle, Muhammad Zaki; Thlama, Bura Paul; Mohd Ali Hanafiah, Muhamad Hakim; Abdullah, Faez Firdaus Jesse; Kamaludeen, Juriah; Mustafa, Suhaili (Springer Science and Business Media B.V., 2025)
Antimicrobial resistance (AMR) in respiratory pathogens of ruminants is a growing threat to animal health, veterinary treatment efficacy, and food production. However, consolidated global data on the prevalence and molecular mechanisms of AMR in these pathogens remain limited, particularly across diverse regions and livestock systems. This systematic review aimed to evaluate the prevalence and molecular mechanisms of AMR in bacterial pathogens responsible for respiratory infections in ruminants. A comprehensive search of PubMed, Scopus, Web of Science, and Google Scholar was conducted to identify English-language, peer-reviewed articles published between January 1, 2020, and May 31, 2025. Eligible studies reported on AMR prevalence and/or mechanisms in respiratory pathogens isolated from cattle, sheep, goats, and buffaloes. Study screening, data extraction, and quality appraisal were performed according to PRISMA guidelines, using the Joanna Briggs Institute (JBI) checklist. Fifty studies met the inclusion criteria, covering bacterial isolates from Africa, Asia, Europe, the Americas, and Oceania. Resistance prevalence ranged from 0.8% to 100%, with Mannheimia haemolytica, Pasteurella multocida, Histophilus somni, and Mycoplasma bovis being the most frequently reported pathogens. Resistance was most common against tetracyclines, macrolides, sulfonamides, and β-lactams. Identified mechanisms included β-lactamase production, such as blaROB-1, blaTEM, efflux pumps msr(E), tet(H), target-site mutations gyrA, parC, 23 S rRNA, and horizontal gene transfer via plasmids and integrative and conjugative elements. This review underscores the global burden of AMR and multidrug resistance in ruminant respiratory pathogens and their potential zoonotic implications. Strengthening molecular surveillance, harmonising diagnostic standards, and integrating antimicrobial usage data, especially in underrepresented regions such as Southeast Asia, are essential to inform targeted interventions.